Durbachite-like melagranite in taiping pluton of bintang batholith, Peninsular Malaysia - Quek, L.X. (Geological Society of Malaysia, 2016)
Durbachite-type rocks are recently found in Taiping Pluton, Bintang Batholith, Peninsular Malaysia. Taiping durbachite-type rocks can be described as K-Mg rich, megacrystic to porphyritic, coarse grained melagranite. The melagranite also contain numerous biotite-rich enclaves/xenoliths of igneous appearance. Petrographic examination shows the rocks contain granite felsic mineral proportion with high amount of biotite, amphiboles with pyroxene relics and traces of pyroxene. The samples are ultrapotassic and most are intermediate in SiO2 composition (59.2 - 65.5 wt. ) but show high MgO (3.0 - 6.4 wt. ) and Cr (233 - 568 ppm). They are also high in certain incompatible elements (Ba, Zr, Rb, Th) and LREE. In general, the durbachite-type rocks geochemistry is comparable to the Central European durbachite suite. The durbachite-type rocks petrogenesis is believed to be complex, requiring a crustal component and enriched lithospheric mantle source. Taiping Pluton itself is located at the Sibumasu plate and U-Pb zircon dating results (218 Â± 1.3 Ma) indicate that the melagranite are emplaced during the Triassic Sibumasu-Indochina collision (200 - 220Ma), which most of the Main Range Granite province are emplaced. It is possible that the Taiping durbachite-type rocks emplacement setting is similar to Central European durbachite suite. Â© 2016, Geological Society of Malaysia. All rights reserved.